PERSEPSI PENUMPANG TERHADAP PENERAPAN BAGASI BERBAYAR MASKAPAI WINGS AIR DI BANDAR UDARA HAJJI HASSAN AROEBOSMAN ENDE - Yulita Mbu Alo, Kristiana; Fauziah Novianty, Rezty (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The purpose of this study is to ascertain how travelers view Wings Air's use of paid luggage at the Hajji Hassan Aroeboesman Ende Airport. Airlines may learn a lot from passenger impressions about the use of paid luggage, including whether aspects of the current policy require further examination. At the Hajji Hassan Aroeboesman Ende Airport, the research was carried out. The study employed a quantitative survey methodology. The population of this study consisted of all Wing Air passengers at Hajji Hassan Aroeboesman Ende Airport; the sample consisted of 100 passengers who used paid luggage. Pearson Product Moment was used to assess the validity of the questionnaire technique in obtaining the data, as well as the validity of it using Cronbach's Alpha. In order to determine the category of passenger perception, the mean value of the test variable was calculated using descriptive analytic techniques on the gathered data. With a mean score of 3.23, the study's findings demonstrated that passengers' perceptions of the Hajji Hassan Aroeboesman Airport's implementation of paid luggage were deemed